Non-combustible electrolyte of lithium ion battery as well as preparation method and application of non-combustible electrolyte
By adding fluorophosphate and aluminum isopropoxide to the lithium-ion battery electrolyte to form a stable protective film, the poor safety performance and flammability of the lithium-ion battery electrolyte are solved, and the battery performance with high safety and long life is achieved.
Patent Information
- Application Number
- CN202411715609.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-11
AI Technical Summary
The existing lithium-ion battery electrolyte has problems such as poor safety performance, high flammability, low lithium ion conductivity and poor electrode interface stability in terms of high safety and long life.
A non-combustible electrolyte of lithium-ion battery including organic solvents, lithium salts, fluorophosphate esters and film-forming additive aluminum isopropoxide is used to form a solid protective film, improving the safety and circulation stability of the battery through thermal decomposition of phosphate-based flame retardants and coordination polymerization reaction of aluminum isopropoxide.
It achieves complete flame retardant of the battery, maintains high cycle performance, significantly improves the service life of the battery, and reduces production costs, making it suitable for large-scale industrial production.
Smart Images

Figure CN119601770A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolyte preparation, and in particular to a non-flammable electrolyte for lithium ion batteries and a preparation method and application thereof. Background Art
[0002] Traditional fossil fuels will release harmful substances such as NO2, SO2, and CO during the mining and utilization process, causing great harm to the environment. Using new energy to replace traditional energy is one of the main ways to improve environmental pollution. Lithium-ion batteries have high specific energy, high operating voltage, and long cycle life, and are suitable for consumer electronic products such as mobile phones, tablets, and computers. However, there are safety and technical problems in the application of high-capacity lithium-ion batteries. With the large-scale promotion and application of lithium-ion batteries, a large number of safety accidents related to thermal runaway of lithium-ion batteries occur every year around the world. Especially during the charging and discharging process, due to the hidden dangers inside the battery and external environmental conditions, it is easy to cause fire and explosion. The electrolyte plays a very critical role in the thermal runaway process of lithium-ion batteries and is one of the key elements of internal fire and explosion.
[0003] At present, common lithium-ion battery electrolytes can be roughly divided into two types: ethers and esters. Ester electrolytes have high electrochemical stability and high ion conductivity, can work in a wide voltage range, help to improve the cycle life of the battery, and have a wider redox potential range, which can adapt to different types of electrode materials. Therefore, ester electrolytes have broad application prospects in the fields of electric vehicles and renewable energy, especially in application scenarios that require high safety and long-life batteries. However, traditional carbonate electrolytes are composed of organic solvents such as ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). They have low flash points and flammability and are prone to fire. In order to improve the fire safety of lithium-ion batteries and solve the problems of low lithium ion conductivity, large electrolyte-electrode interface impedance, and poor stability with the electrode interface caused by excessive additives in existing electrolytes, high-safety non-flammable electrolytes are the most economical and simple strategy, and the development of non-flammable electrolyte multifunctional additives has become an important research topic. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a non-flammable electrolyte for lithium-ion batteries and a preparation method and application thereof, so as to solve the problem of poor safety performance of existing electrolytes.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: a non-flammable electrolyte for lithium-ion batteries is provided, comprising: an organic solvent, a lithium salt, a fluorophosphate ester and a film-forming additive, wherein the film-forming additive is aluminum isopropoxide.
[0006] On the basis of the above technical solution, the present invention can also be improved as follows:
[0007] Furthermore, the organic solvent includes cyclic carbonate and linear carbonate, the cyclic carbonate is at least one of ethylene carbonate and propylene carbonate, and the linear carbonate is at least one of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
[0008] Furthermore, the volume ratio of the cyclic carbonate to the linear carbonate is 1-2:1-2.
[0009] Furthermore, the lithium salt is at least one of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium dioxalatoborate, lithium bis(trifluoromethylsulfonylimide) and lithium bis(fluorosulfonylimide).
[0010] Furthermore, the lithium salt is lithium hexafluorophosphate.
[0011] Furthermore, the fluorophosphate is tris(2,2,2-trifluoroethyl)phosphate.
[0012] Furthermore, the concentration of lithium salt in the electrolyte is 0.5-2 mol / L.
[0013] Furthermore, the concentration of lithium salt in the electrolyte is 0.8-1.2 mol / L.
[0014] Furthermore, the concentration of the fluorophosphate in the electrolyte is 8-20 wt %.
[0015] Furthermore, the concentration of the fluorophosphate in the electrolyte is 8 wt %.
[0016] Furthermore, the concentration of the film-forming additive in the electrolyte is 0.5-2 wt %.
[0017] Furthermore, the concentration of the film-forming additive in the electrolyte is 1 wt %.
[0018] The present invention also provides a method for preparing the above-mentioned non-flammable electrolyte for lithium ion batteries, comprising the following steps:
[0019] (1) mixing an organic solvent and a lithium salt, heating and stirring, to prepare a basic electrolyte;
[0020] (2) Adding fluorophosphate and film-forming additives to the basic electrolyte prepared in step (1), heating and stirring, to prepare a non-flammable electrolyte for lithium-ion batteries.
[0021] Furthermore, steps (1)-(2) are carried out under an argon atmosphere, and the concentrations of water and oxygen are both less than 0.1 ppm.
[0022] Furthermore, in steps (1)-(2), the heating temperature is 30-50°C.
[0023] Furthermore, in steps (1)-(2), the stirring speed is 300-500 rpm and the stirring time is 4-6 hours.
[0024] The present invention also provides application of the non-flammable electrolyte for lithium ion batteries in the preparation of lithium ion batteries.
[0025] The present invention has the following beneficial effects:
[0026] 1. The flame retardant mechanism of phosphate flame retardants in liquid state is mainly as follows: when the material is burned by fire, the phosphate decomposes through heat, and the phosphorus element reacts with the free radicals produced by combustion to generate unstable phosphate free radicals, forming a large number of phosphorus oxygen intermediates, and finally obtaining stable phosphate oxides in the air, which absorb heat to reduce the system temperature, thereby inhibiting the combustion reaction.
[0027] The present invention uses tris (2,2,2-trifluoroethyl) phosphate as a flame retardant additive, but has the following disadvantages: in order to make the electrolyte completely flame retardant, the amount of the flame retardant additive tris (2,2,2-trifluoroethyl) phosphate needs to reach ≥ 8% of the mass fraction of the electrolyte. Excessive addition of tris (2,2,2-trifluoroethyl) phosphate leads to an increase in electrolyte viscosity, which directly affects the transmission efficiency of lithium ions. This is because high viscosity slows down the migration speed of ions in the electrolyte and also leads to an increase in the internal resistance of the battery. In addition, the increase in electrolyte viscosity and the decrease in conductivity will be aggravated under low temperature conditions, further affecting the charge and discharge efficiency of the battery. The severe degradation of the surface area makes it impossible to form an effective passivation film (such as SEI film) to protect the electrode material, resulting in the intensification of the side reactions between the surface of the positive electrode material and the electrolyte. These side reactions not only consume the active ingredients in the electrolyte, but also may produce irreversible chemical changes, thereby leading to a reduction in the energy density of the battery. Ultimately, these factors work together to reduce the rate performance and discharge capacity of the battery, affecting the overall electrochemical performance of the battery. Aluminum isopropoxide (AIP) is used as an initiator. – The group has strong nucleophilicity and can 3+ The coordination polymerization reaction of ethylene carbonate (EC) or propylene carbonate (PC) is induced by the combination of ethylene carbonate (EC) or propylene carbonate (PC), resulting in the formation of a strong and strong CEI on the surface of the positive electrode material, effectively mitigating the negative effects of tris (2,2,2-trifluoroethyl) phosphate (TFEP). The present invention compounds TFEP and AIP, which can maintain the long-cycle stability of the battery while making the electrolyte completely flame-retardant.
[0028] 2. The preparation method of the present invention is simple, has mild conditions, and is low in cost, and is suitable for large-scale industrial production. It meets the existing market requirements for the non-flammable and high safety performance of the electrolyte, and has a relatively broad application and production prospect.
[0029] 3. The present invention provides a non-flammable and highly safe electrolyte with high cycle performance, in which tri(2,2,2-trifluoroethyl) phosphate is added as a highly safe flame retardant. Compared with the basic solvents propylene carbonate (-8.114eV), ethylene carbonate (-8.466eV) and ethyl methyl carbonate (-8.131eV), the HOMO energy level (-7.762eV) is higher, and it is more inclined to undergo oxidation reaction at the positive electrode to form a CEI film rich in inorganic components such as fluorine (F) and phosphorus (P). This CEI film plays an important role in protecting the positive electrode material and maintaining the stability of the battery. At the same time, compared with the basic solvent propylene carbonate (0.071eV), ethylene carbonate (-0.284V) and ethyl methyl carbonate (0.067eV) have a lower LUMO energy level (-0.848eV), which can show stronger reduction stability at the negative electrode, and help to form a stable SEI film. These inorganic components can promote lithium ions (Li + ) is quickly transported, thereby improving the electrochemical performance and thermal stability of the battery. In addition, through the screening of solvents, the amount of the flame retardant additive tris (2,2,2-trifluoroethyl) phosphate is greatly reduced, which effectively alleviates the problems of large interface impedance and poor stability with the electrode interface during the charge and discharge process, and also has certain ecological and environmental protection value; aluminum isopropoxide has a moderate dielectric constant and desolvation energy as a film-forming additive, which means that aluminum isopropoxide can be effectively polarized in the electric field, thereby promoting the migration of ions in the electrolyte and the formation of a stable film; secondly, aluminum isopropoxide can reduce the orderly arrangement of solvent molecules around ions in the electrolyte, thereby reducing the energy barrier of ion migration and increasing the transmission rate of lithium ions. The combination of the above two additives can play a synergistic role. When adapted to high-energy-density lithium-rich manganese positive electrode materials, it not only makes the electrolyte non-flammable, but also can obtain a higher capacity, maintain excellent cycle performance, and significantly improve the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a flame retardant test chart of electrolyte with different flame retardant additive addition amounts.
[0031] Figure 2 This is a graph showing the first cycle charge and discharge capacity test results of the electrolyte high-voltage lithium-ion batteries of Examples 1, 2, 5 and Comparative Examples 1 and 7.
[0032] Figure 3 The graph shows the test results of capacity retention and coulombic efficiency of high-voltage lithium-ion batteries of the electrolytes of Examples 1, 3, 5 and Comparative Examples 1 and 3.
[0033] Figure 4 This is a graph showing the rate performance test results of high-voltage lithium-ion batteries using electrolytes of Examples 1, 3, 5 and Comparative Example 1.
[0034] Figure 5This is a graph showing the test results of the charge and discharge curve of the electrolyte high-voltage lithium-ion battery of Example 1.
[0035] Figure 6 This is a graph showing the test results of the charge and discharge curve of the electrolyte high-voltage lithium-ion battery of Comparative Example 1.
[0036] Figure 7 This is a graph showing the test results of the cyclic voltammetry curve of the high-voltage lithium-ion battery with the electrolyte in Example 1.
[0037] Figure 8 This is a graph showing the test results of the cyclic voltammetry curve of the high-voltage lithium-ion battery with the electrolyte of Comparative Example 1.
[0038] Fig. 9 This is a graph showing the reversibility test results of Li deposition / precipitation of Li||Li symmetric batteries with electrolytes of Example 1 and Comparative Examples 1 and 3.
[0039] Fig.10 Graph showing the Li deposition / sedimentation stability test results of the electrolyte Li||Cu battery of Examples 1, 3, 5 and Comparative Example 1.
[0040] Fig.11 This is the interface XPS analysis of the high-voltage lithium-ion battery with the electrolyte in Comparative Example 1 after 200 cycles.
[0041] Fig.12 This is the interface XPS analysis of the high-voltage lithium-ion battery with the electrolyte in Example 1 after 200 cycles.
[0042] Fig.13 These are SEM images of the lithium-rich manganese pole pieces of the electrolyte high-voltage lithium-ion batteries of Example 1 and Comparative Example 1 after 200 cycles.
[0043] Fig.14 This is a TEM image of the lithium-manganese-rich electrode of the high-voltage lithium-ion battery with the electrolyte in comparative example 1 after 200 cycles.
[0044] Fig.15 This is a TEM image of the lithium-manganese-rich electrode of the high-voltage lithium-ion battery with the electrolyte in Example 1 after 200 cycles. DETAILED DESCRIPTION
[0045] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0046] The structural formula of tris(2,2,2-trifluoroethyl) phosphate is
[0047] The structural formula of aluminum isopropoxide is
[0048] Embodiment 1:
[0049] A non-flammable electrolyte for lithium-ion batteries, comprising an organic solvent (ethylene carbonate EC, propylene carbonate PC and ethyl methyl carbonate EMC in a volume ratio of 1:1:1), a lithium salt (lithium hexafluorophosphate, LiPF6), a fluorophosphate ester (tris(2,2,2-trifluoroethyl) phosphate) and a film-forming additive (aluminum isopropoxide). The concentration of the lithium salt in the electrolyte is 1 mol / L; the concentration of the fluorophosphate ester is 8 wt%; and the concentration of the film-forming additive is 1 wt%.
[0050] A method for preparing a non-flammable electrolyte for a lithium-ion battery comprises the following steps:
[0051] (1) In a glove box under an argon atmosphere (H2O≤0.01ppm, O2≤0.01ppm), an organic solvent and a lithium salt are mixed, added into a PP bottle, heated and stirred to prepare a basic electrolyte;
[0052] (2) Adding fluorophosphate and film-forming additives to the basic electrolyte prepared in step (1), adding a magnet at 40° C., stirring at 300 rpm on a magnetic stirrer for 6 hours to prepare a non-flammable electrolyte for lithium-ion batteries.
[0053] Embodiment 2:
[0054] A non-flammable electrolyte for lithium ion batteries, wherein the concentration of fluorophosphate is 12wt%; the concentration of film-forming additive is 1wt%, and the rest is the same as in Example 1.
[0055] A method for preparing a non-flammable electrolyte for a lithium ion battery comprises the following steps: same as in Example 1.
[0056] Embodiment 3:
[0057] A non-flammable electrolyte for lithium ion batteries includes lithium salt (lithium bis(oxalatoborate, LiBOB), wherein the concentration of fluorophosphate is 10wt%; the concentration of film-forming additive is 0.5wt%, and the rest is the same as in Example 1.
[0058] A method for preparing a non-flammable electrolyte for a lithium ion battery comprises the following steps: same as in Example 1.
[0059] Embodiment 4:
[0060] A non-flammable electrolyte for lithium-ion batteries, comprising an organic solvent (ethylene carbonate EC, diethyl carbonate DEC and ethyl methyl carbonate EMC in a volume ratio of 5:2:3). The concentration of lithium salt in the electrolyte is 1.2 mol / L; the concentration of fluorophosphate is 15 wt%; the concentration of film-forming additive is 1 wt%, and the rest is the same as in Example 1.
[0061] A method for preparing a non-flammable electrolyte for a lithium ion battery comprises the following steps: same as in Example 1.
[0062] Embodiment 5:
[0063] A non-flammable electrolyte for lithium-ion batteries includes an organic solvent (ethylene carbonate EC, propylene carbonate PC and diethyl carbonate DEC in a volume ratio of 1:1:1), wherein the concentration of the fluorophosphate is 10wt%; the concentration of the film-forming additive is 1wt%, and the rest is the same as in Example 1.
[0064] A method for preparing a non-flammable electrolyte for a lithium ion battery comprises the following steps: same as in Example 1.
[0065] Embodiment 6:
[0066] A non-flammable electrolyte for lithium-ion batteries, comprising an organic solvent (ethylene carbonate EC, diethyl carbonate DEC and ethyl methyl carbonate EMC in a volume ratio of 1:1:1) and a lithium salt (lithium difluorooxalatoborate, LiDFOB). The concentration of the lithium salt in the electrolyte is 0.8 mol / L; the concentration of the fluorophosphate is 15 wt%; and the concentration of the film-forming additive is 0.8 wt%.
[0067] A method for preparing a non-flammable electrolyte for a lithium ion battery comprises the following steps: same as in Example 1.
[0068] Embodiment 7:
[0069] A non-flammable electrolyte for a lithium-ion battery comprises an organic solvent (ethylene carbonate EC, propylene carbonate PC and diethyl carbonate DEC in a volume ratio of 1:1:1) and a lithium salt (lithium difluorooxalatoborate, LiDFOB); wherein the concentration of the lithium salt in the electrolyte is 1.2 mol / L; the concentration of the fluorophosphate is 12 wt%; and the concentration of the film-forming additive is 0.8 wt%.
[0070] A method for preparing a non-flammable electrolyte for a lithium ion battery comprises the following steps: same as in Example 1.
[0071] Embodiment 8:
[0072] A non-flammable electrolyte for lithium-ion batteries, comprising an organic solvent (ethylene carbonate, propylene carbonate, dimethyl carbonate), a lithium salt (lithium tetrafluoroborate), a fluorophosphate (tris(2,2,2-trifluoroethyl) phosphate) and a film-forming additive (aluminum isopropoxide). The concentration of the lithium salt in the electrolyte is 0.5 mol / L; the concentration of the fluorophosphate is 8 wt%; and the concentration of the film-forming additive is 0.5 wt%.
[0073] A method for preparing a non-flammable electrolyte for a lithium-ion battery comprises the following steps:
[0074] (1) In a glove box under an argon atmosphere (H2O≤0.01ppm, O2≤0.01ppm), an organic solvent and a lithium salt are mixed, heated and stirred to prepare a basic electrolyte;
[0075] (2) Adding fluorophosphate and a film-forming additive to the basic electrolyte prepared in step (1), adding a magnet at 30° C., stirring on a magnetic stirrer at 400 rpm for 5 h, and preparing a non-flammable electrolyte for lithium-ion batteries.
[0076] Embodiment 9:
[0077] A non-flammable electrolyte for lithium-ion batteries, comprising an organic solvent (ethylene carbonate and ethyl methyl carbonate), a lithium salt (lithium bistrifluoromethylsulfonyl imide), a fluorophosphate (tris(2,2,2-trifluoroethyl) phosphate) and a film-forming additive (aluminum isopropoxide). The concentration of the lithium salt in the electrolyte is 2 mol / L; the concentration of the fluorophosphate is 20 wt%; and the concentration of the film-forming additive is 2 wt%.
[0078] A method for preparing a non-flammable electrolyte for a lithium-ion battery comprises the following steps:
[0079] (1) In a glove box under an argon atmosphere (H2O≤0.01ppm, O2≤0.01ppm), an organic solvent and a lithium salt are mixed, heated and stirred to prepare a basic electrolyte;
[0080] (2) Adding fluorophosphate and a film-forming additive to the basic electrolyte prepared in step (1), adding a magnet at 50° C., stirring on a magnetic stirrer at 500 rpm for 4 hours to prepare a non-flammable electrolyte for lithium-ion batteries.
[0081] Comparative Example 1:
[0082] A lithium ion battery electrolyte does not include fluorophosphate (tris(2,2,2-trifluoroethyl) phosphate) and a film-forming additive (aluminum isopropoxide), and the rest is the same as in Example 1.
[0083] A method for preparing a lithium ion battery electrolyte comprises the following steps: same as in Example 1.
[0084] Comparative Example 2:
[0085] A lithium ion battery electrolyte does not include a film-forming additive (aluminum isopropoxide), and the rest is the same as in Example 1.
[0086] A method for preparing a lithium ion battery electrolyte comprises the following steps: same as in Example 1.
[0087] Comparative Example 3:
[0088] A lithium ion battery electrolyte does not include fluorophosphate (tris(2,2,2-trifluoroethyl) phosphate), and the rest is the same as in Example 1.
[0089] A method for preparing a lithium ion battery electrolyte comprises the following steps: same as in Example 1.
[0090] Comparative Example 4:
[0091] A lithium ion battery electrolyte, wherein the concentration of fluorophosphate is 6wt%; the concentration of film-forming additive is 0.5wt%, and the rest is the same as in Example 1.
[0092] A method for preparing a lithium ion battery electrolyte comprises the following steps: same as in Example 1.
[0093] Comparative Example 5:
[0094] A lithium ion battery electrolyte comprises lithium salt (lithium difluorooxalatoborate, LiDFOB); wherein the concentration of the lithium salt in the electrolyte is 1.2 mol / L; the concentration of the fluorophosphate is 5 wt%; the concentration of the film-forming additive is 1 wt%, and the rest is the same as in Example 1.
[0095] A method for preparing a lithium ion battery electrolyte comprises the following steps: same as in Example 1.
[0096] Comparative Example 6:
[0097] A lithium ion battery electrolyte comprises a lithium salt (lithium bis(oxalatoborate, LiBOB); the concentration of fluorophosphate is 4wt%; the concentration of film-forming additive is 1.2wt%, and the rest is the same as in Example 1.
[0098] A method for preparing a lithium ion battery electrolyte comprises the following steps: same as in Example 1.
[0099] Comparative Example 7:
[0100] A lithium-ion battery electrolyte comprises an organic solvent (ethylene carbonate EC, diethyl carbonate DEC and ethyl methyl carbonate EMC in a volume ratio of 5:2:3) and a lithium salt (lithium difluorooxalatoborate, LiDFOB). The concentration of the lithium salt in the electrolyte is 0.8 mol / L; the concentration of the fluorophosphate is 6 wt%; the concentration of the film-forming additive is 1.2 wt%, and the rest is the same as in Example 1.
[0101] A method for preparing a lithium ion battery electrolyte comprises the following steps: same as in Example 1.
[0102] Comparative Example 8:
[0103] A lithium-ion battery electrolyte comprises an organic solvent (ethylene carbonate EC, diethyl carbonate DEC and ethyl methyl carbonate EMC in a volume ratio of 5:2:3) and a lithium salt (lithium bis(fluorosulfonyl)imide, LiFSI). The concentration of the fluorophosphate is 5wt%; the concentration of the film-forming additive is 0.5wt%, and the rest is the same as in Example 1.
[0104] A method for preparing a lithium ion battery electrolyte comprises the following steps: same as in Example 1.
[0105] Test example
[0106] 1. Flame retardancy
[0107] Measuring the flammability of electrolyte: Cut 5mm thick ceramic fiber paper into 15mm×6mm strips, place in an oven at 80℃ and dry for 8h; Take the dried ceramic fiber paper and hook it with aluminum wire, weigh the weight as m1, let the electrolyte soak the ceramic fiber paper for 5min, record the mass of the absorbed liquid, weigh the weight as m2, and the weighing accuracy is 0.001g; Ignite the ceramic fiber paper soaked in electrolyte, and record the time from the fire source leaving to the ceramic fiber paper extinguishing as t; Conduct 6 experiments for each experimental sample, and obtain its SET value based on the time required for the unit mass of electrolyte to continue to burn. SET=t / (m2-m1), generally speaking, when SET<6s g –1 , the electrolyte is considered "non-flammable"; when 6s g –1 <SET<20s g –1 , it is considered as "flame retardant"; when SET>6s g –1 , it is considered "flammable".
[0108] 2. Electrochemical performance
[0109] In order to test the performance of the electrolyte, the electrolyte of the present invention is used to assemble a high-voltage lithium-ion battery (LRMO||Li half-cell). The battery assembly is as follows: a button-type half-cell is made in a glove box filled with argon. The separator is Celgard2500, the half-cell is a pole piece to a lithium sheet, the positive electrode is a lithium-rich manganese base (xLi2MnO3(1-x)LiMnO2), and the negative electrode is a lithium sheet. The packaged battery is taken out and placed in an oven at 45°C for 40 hours. 。
[0110] Then physical and electrochemical cycle tests were carried out (the battery was cycled 800 times at a high voltage of 4.8V to maintain capacity), and the test method used was the 2025 button battery test.
[0111] The results are shown in Table 1.
[0112] Table 1 Electrolyte performance test
[0113]
[0114] As can be seen from Table 1, from the corresponding self-extinguishing time, it can be seen that the electrolyte containing the fluorophosphate ester of the present application has better safety and non-flammability; the electrolyte containing the film-forming additive of the present application has better cycle performance; the electrolyte containing both has better safety and non-flammability and capacity retention rate.
[0115] It can be seen from the self-extinguishing time corresponding to Example 1, Comparative Example 3 and Comparative Examples 4-7 that the electrolyte is non-flammable when the mass fraction of the flame retardant tris(2,2,2-trifluoroethyl) phosphate TFEP is 8%, which is the minimum amount of flame retardant added to achieve non-flammable electrolyte.
[0116] 3. Add fluorinated phosphate to Comparative Example 1 at a concentration of 1-10 wt% (integer), and then test its flame retardancy using the same testing method as in "1. Flame retardancy". The results are shown in Figure 1 .
[0117] Depend on Figure 1 It can be seen that the electrolyte is non-flammable when the mass fraction of the flame retardant tris(2,2,2-trifluoroethyl) phosphate TFEP is 8%, which is the minimum amount of flame retardant added to achieve non-flammable electrolyte.
[0118] 4. The electrolytes prepared in Examples 1, 2, and 5 and the electrolytes prepared in Comparative Examples 1 and 7 were assembled into high-voltage lithium-ion batteries (LRMO||Li half-cells) and the first cycle charge and discharge test was performed. The specific detection method is as follows: the assembled button batteries were tested for constant current charge and discharge performance at 25°C using the Xinwei CT-4008Tn test system. The test voltage was 2V-4.8V, and the first cycle charge and discharge test was performed at a current density of 0.1C. The results are shown in Figure 2 .
[0119] Depend on Figure 2 It can be seen that the first discharge specific capacity of the electrolytes prepared in Comparative Example 1 and Comparative Example 7 are 260.1 mAh / g and 262.3 mAh / g, respectively; while the first discharge specific capacity of the electrolytes prepared in Comparative Example 1, Comparative Example 2 and Comparative Example 5 are 300.4 mAh / g, 301.1 mAh / g and 310.3 mAh / g, respectively; the battery corresponding to the electrolyte prepared in Example 1 to which an appropriate amount of tri(2,2,2-trifluoroethyl) phosphate and aluminum isopropoxide were added exhibits a high first-cycle coulomb efficiency of 88.5%, which is significantly higher than the first-cycle coulomb efficiency of 77.5% of the basic electrolyte in Comparative Example 1.
[0120] 5. The electrolytes prepared in Examples 1, 3, and 5 and the electrolytes prepared in Comparative Examples 1 and 3 were assembled into high-voltage lithium-ion batteries (LRMO||Li half-cells) and the capacity retention rate was tested. The specific detection method is as follows: the assembled button-type batteries were tested for constant current cycle performance at 25°C using the Xinwei CT-4008Tn test system. The test voltage was 2V-4.8V, and the batteries were activated for three cycles at a current density of 0.1C. After discharge, the batteries were allowed to stand for 2 hours, and then cycled at a current density of 1C. The percentage obtained by dividing the discharge capacity at the 800th discharge by the maximum discharge capacity is the capacity retention rate (%) of the battery. See the results. Figure 3 .
[0121] Depend on Figure 3 It can be seen that the battery corresponding to the electrolyte prepared in comparative example 1 has a discharge capacity of 57 mAh / g and a capacity retention rate of 26.1% after 800 cycles of the experiment; the battery corresponding to the electrolyte prepared in comparative example 3 has a discharge capacity of 64 mAh / g and a capacity retention rate of 30.2% after 800 cycles of the experiment; and the battery corresponding to the electrolyte prepared in Example 1 with the addition of an appropriate amount of tris(2,2,2-trifluoroethyl) phosphate and aluminum isopropoxide has a discharge capacity of 182.3 mAh / g and a capacity retention rate of 81.6% after 800 cycles, and an average CE of 99.2%, which is significantly higher than the capacity retention rate and average CE of the batteries in comparative examples 1 and 3. This shows that the membrane additive of the present application can improve the stability of the positive and negative electrodes of the battery in the electrolyte, achieve a good capacity retention rate, and effectively improve the service life of the battery.
[0122] 6. The electrolytes prepared in Examples 1, 3, and 5 and the electrolyte prepared in Comparative Example 1 were assembled into high-voltage lithium-ion batteries (LRMO||Li half-cells) for rate testing. The specific detection method is as follows: the assembled button-type batteries were tested for charge and discharge performance at different currents using the Xinwei CT-4008Tn test system at 25°C. The test voltage was 2V-4.8V and the current density was 0.1C, 0.5C, 1C, 2C, 5C and 0.1C. The results are shown in Figure 4 .
[0123] Depend on Figure 4 It can be seen that the discharge specific capacities of the electrolyte prepared in Comparative Example 1 at 0.1C, 0.5C, 1C, 2C and 5C are 271mAh / g, 216mAh / g, 190mAh / g, 162mAh / g and 127mAh / g respectively, and the discharge specific capacity at 0.1C after 25 cycles is 254mAh / g, and the capacity retention rate is 93.7%; while the electrolyte prepared in Example 1 to which an appropriate amount of tris(2,2,2-trifluoroethyl) phosphate and aluminum isopropoxide are added has a corresponding capacity of 271mAh / g, 216mAh / g, 190mAh / g, 162mAh / g and 127mAh / g respectively. The discharge specific capacities of the battery at 0.1C, 0.5C, 1C, 2C and 5C are 295mAh / g, 244mAh / g, 217mAh / g, 185mAh / g and 150mAh / g respectively, and the discharge specific capacity at 0.1C after 25 cycles is 287mAh / g, and the capacity retention rate is 97.3%, which is significantly better than that of Comparative Example 1. The results show that the present invention effectively reduces the polarization of the battery, improves the rate performance of the battery, and the battery recovery at different rates is also better.
[0124] 7. The operating voltage refers to the potential difference between the positive and negative electrodes of the battery when the battery is in working condition, that is, when current flows through the circuit. The horizontal axis of the capacity-voltage curve reflects the battery's charge and discharge capacity, state of charge and other information, while the vertical axis contains the battery's voltage platform, inflection point, polarization and other information. During the charge and discharge process of lithium batteries, voltage decay is inevitable. It is necessary to study the changes in charge and discharge capacity at different numbers of cycles and to analyze the voltage conditions based on the charge and discharge curves. The electrolytes of Comparative Example 1 and Example 1 were respectively assembled into high-voltage lithium-ion batteries (LRMO||Li half-cells), and charge and discharge curve tests of different numbers of cycles were performed. The specific detection method is as follows: Use the Xinwei CT-4008Tn test system to perform a constant current charge and discharge performance test on the assembled button batteries at 25°C. The test voltage is 2V-4.8V, and the charge and discharge curves of the 1st, 4th, 50th, 100th, 300th, 500th, and 800th cycles are selected to compare the capacity and voltage. See the results. Figure 5-6 .
[0125] Depend on Figure 5-6 It can be seen that as the charge and discharge cycle proceeds, the discharge platforms of Comparative Example 1 and Example 1 both show varying degrees of decay, but the charge and discharge voltage platform of Comparative Example 1 is more shifted to the left, the initial charge point separation is more obvious, and the decay rate is significantly faster than that of Example 1, indicating that the voltage decay of the battery corresponding to the electrolyte prepared in Example 1 to which an appropriate amount of tris(2,2,2-trifluoroethyl) phosphate and aluminum isopropoxide are added is significantly suppressed.
[0126] 8. The cyclic voltammetry curve can be used to analyze the electrochemical reaction behavior of the research material according to the changes in each platform area. The oxidation peak and reduction peak in the curve correspond to the charging platform and discharging platform in the charge-discharge curve, and have a corresponding relationship with the oxidation peak and reduction peak in the cyclic voltammetry curve. If the total capacity of charging and discharging is the same, but the capacity of each corresponding platform / slope is different, it means that the thermodynamic reaction path of lithium insertion and extraction or the kinetic characteristics of lithium insertion and extraction of the material are significantly different. The electrolytes of Comparative Example 1 and Example 1 were respectively assembled into high-voltage lithium-ion batteries (LRMO||Li half-cells), and cyclic voltammetry curve tests of different numbers of cycles were performed. The specific detection method is as follows: Use the Xinwei CT-4008Tn test system to perform constant current charge and discharge performance tests on the assembled button batteries at 25°C. The test voltage is 2V-4.8V, and the test is performed at a current density of 0.1C. The charge and discharge curves of the first three cycles were selected for comparison of the charge and discharge platforms. See the results. Figure 7-8 .
[0127] Depend on Figure 7-8 It can be seen that the voltage hysteresis of the battery of Comparative Example 1 using the basic electrolyte is relatively wide, at 0.35 V, and the voltage hysteresis of the battery corresponding to the electrolyte prepared in Example 1 with the addition of an appropriate amount of tris(2,2,2-trifluoroethyl) phosphate and aluminum isopropoxide is 0.3 V. In contrast, the narrower voltage hysteresis obtained in Example 1 confirms its fast reaction kinetics, which is consistent with Figure 4 The rate performance tests shown are consistent, indicating that the battery of Example 1 has excellent cycle stability.
[0128] 9. The electrolytes of Example 1 and Comparative Examples 1 and 3 were used to assemble Li||Li symmetrical batteries. The batteries were CR2025 button-type half-cells. Both the positive and negative electrodes were commercial lithium sheets. The packaged batteries were taken out and placed in an oven at 45°C for 40 hours. The reversibility of Li deposition / precipitation behavior was evaluated. Results are shown in Fig. 9 .
[0129] Depend on Fig. 9 It can be seen that at a current density of 1 mA cm -2 , with an area capacity of 1 mAh cm -2In the case of Comparative Example 1, as the cycle progresses, the Li||Li symmetric battery using the basic electrolyte has a huge voltage fluctuation after only about 300 hours of cycling, and the voltage polarization increases sharply. This is due to the increase in resistance caused by the serious side reaction between the electrolyte and lithium. Although the battery corresponding to the electrolyte of Comparative Example 3, which only adds an appropriate amount of tris(2,2,2-trifluoroethyl) phosphate, achieves a flame retardant effect, the overpotential still increases strongly with the increase in cycles. In contrast, the battery corresponding to the electrolyte prepared in Example 1, which adds an appropriate amount of tris(2,2,2-trifluoroethyl) phosphate and aluminum isopropoxide, exhibits the best reversibility, showing stable lithium plating / stripping for more than 800 hours, the longest cycle time, and the lowest overpotential. These results show that even a small amount of AIP (1%) addition can significantly improve the reversible deposition behavior of lithium, significantly inhibit the side reaction between Li and the electrolyte, and promote the uniform deposition of lithium, promote the formation of a stable SEI, and facilitate the establishment of a more stable interface on the surface of the Li negative electrode, thereby enhancing the plating / stripping behavior of Li ions.
[0130] 10. In order to further study the cyclic stability of lithium plating / stripping, the electrolytes of Examples 1, 3, 5 and Comparative Example 1 were used to assemble Li||Cu batteries. The batteries were CR2025 button-type half-cells. The positive electrode material was commercial Cu foil and the negative electrode material was commercial Li sheet. The packaged batteries were taken out and placed in an oven at 45°C for 40 hours. A constant current cycle test was performed to evaluate the stability of Li deposition / precipitation. The Coulomb efficiency (CE) of lithium plating / stripping can be calculated by the ratio of the amount of lithium stripped to the amount of lithium deposited in each cycle. The results are shown in Fig.10 .
[0131] Depend on Fig.10 It can be seen that at a current density of 1 mA cm -2 , with an area capacity of 1 mAh cm -2 In the case of , Comparative Example 1 using the basic electrolyte Li||Cu showed a significant decrease in CE and unstable cycling. The coulombic efficiency of Example 5 was significantly improved, but instability occurred after 85 cycles, which means that a large amount of Li deposited on the surface of the Cu electrode cannot be stably stripped, showing a greater voltage hysteresis. In contrast, the CE of the Li||Cu batteries of Example 1 and Example 3 was stable at 98% after 120 cycles. This means that the addition of an appropriate amount of tris(2,2,2-trifluoroethyl) phosphate and aluminum isopropoxide is conducive to the deposition of lithium. By forming a uniform and dense lithium deposition layer on the surface of the Cu electrode, the dendrite growth of the lithium metal negative electrode during the charge and discharge process can be significantly inhibited, and the contact area between the electrode and the electrolyte can be effectively reduced, thereby reducing continuous parasitic reactions. In addition, by constructing a lithium-philic matrix on the surface of the Cu electrode, the adhesion between the lithium plating and the electrode matrix can be further enhanced, the morphology of the lithium plating can be improved, and the interface energy between the Cu electrode and the lithium metal can be reduced.
[0132] 11. Assemble button cells using the electrolytes prepared in Example 1 and Comparative Example 1, and perform a charge-discharge cycle test on them for 200 cycles. The positive electrode material used in the test is a lithium-rich manganese-based material, the charge-discharge voltage range is set at 2V-4.8V, and the current density is 0.1C. After the cycle is completed, the electrode sheet is subsequently processed in an argon-filled glove box environment, and then the sample is transferred to the equipment using a transfer chamber. The surface analysis is performed using an ESCALAB Xi+ X-ray photoelectron spectrometer (XPS) produced by Thermo Fisher Scientific, USA, and the data is processed using Avantage software to accurately analyze the elemental composition and chemical state of the material surface. See the results. Figure 11-12 .
[0133] Depend on Figure 11-12 It can be seen that the pole pieces obtained in the experimental groups of Example 1 and Comparative Example 1 after 200 cycles, LixPOyFz peaks of 688.18eV and 686.37eV and LiF peaks of 685.8eV and 684.86eV were detected in the F-1s spectrum. Through comparative analysis, the LiF peak of the electrolyte pole piece of Example 1 is higher than that of Comparative Example 1, and the LixPOyFz peak is lower than that of Comparative Example 1. The LiF-rich electrolyte can form a stable CEI film at the positive electrode, significantly improve the cycle stability under high pressure, and effectively inhibit the harmful oxidative decomposition of the positive electrode material and the dissolution of metal ions (such as Co) in the electrolyte; and the high content of LiF helps to enhance charge transfer, promote the decomposition of lithium salts, form a uniform and dense SEI layer rich in LiF, promote the uniform deposition of lithium, and inhibit the growth of lithium dendrites, thereby improving the cycle stability of the battery. Therefore, after adding an appropriate amount of tris (2,2,2 trifluoroethyl) phosphate and aluminum isopropoxide, the battery cycle stability is significantly improved.
[0134] The lithium salt lithium hexafluorophosphate LiPF6 will undergo hydrolysis reaction in the electrolyte, and the generated hydrolysis products include LiPxFy (135.81eV, 134.12eV) and LixPOyFz. LiPxFy may have a negative impact on battery performance, such as increasing battery internal resistance, affecting energy density and cycle life, and increasing self-discharge rate. In the experimental group of Example 1, the content of organic matter LiPxFy in the CEI film was significantly reduced, indicating that the addition of an appropriate amount of tris (2,2,2-trifluoroethyl) phosphate and aluminum isopropoxide inhibited the decomposition of the electrolyte and protected the positive electrode from the erosion of the electrolyte. LixPOyFz (134.12eV) is considered to have higher oxidation stability than organic / inorganic oxides, which is conducive to the formation of conformal and dense CEI on the positive electrode surface, thereby effectively inhibiting the side reactions between the positive electrode material and the electrolyte and preventing direct contact between the electrolyte and the electrode. In Example 1, the content of organic matter LixPOyFz in the CEI film increased significantly, indicating that the addition of an appropriate amount of tri(2,2,2-trifluoroethyl) phosphate and aluminum isopropoxide can enable the battery to have a higher energy density and excellent rate performance, which is very important for the fast charge and discharge capability of the battery.
[0135] The Al 2p characteristic peaks were tested for the electrolyte electrode of Example 1 and the electrolyte electrode of Comparative Example 1 after cycling. Aluminum isopropoxide (AIP) can be used in the Al 3+ In the presence of ethylene carbonate (EC) or propylene carbonate (PC), a coordination polymerization reaction is induced to form a strong and strong CEI on the surface of the positive electrode material. No peak intensity can be detected in the Al 2p spectrum of the pole piece of comparative example 1, while the pole piece corresponding to embodiment 1 shows a characteristic peak of Al2O3 (75.88eV) after cycling. The excellent chemical inertness and thermal stability of Al2O3 can improve the thermodynamic stability of the diaphragm, and the Al2O3 coating can provide a good electronic insulation layer while allowing lithium ions to pass through, reducing the charge accumulation on the electrode surface, reducing the resistance inside the battery, and improving the charge and discharge efficiency, so that the lithium-rich manganese-lithium battery assembled with the electrolyte after adding an appropriate amount of tris (2,2,2-trifluoroethyl) phosphate and aluminum isopropoxide has good cycle stability and safety.
[0136] 12. The electrolytes of Comparative Example 1 and Example 1 were respectively assembled into high-voltage lithium-ion batteries (LRMO||Li half-cells), and the lithium-rich manganese pole pieces were tested after 200 cycles. The cycle method was the same as described in 7 above.
[0137] Scanning electron microscopy (SEM) uses a narrow focused high-energy electron beam to scan samples, and stimulates various physical information through the interaction between the beam and the material. This information is collected, amplified, and re-imaged to achieve the purpose of characterizing the microscopic morphology of the material. Using a scanning electron microscope to analyze the surface morphology of lithium-rich manganese-based electrode materials after 200 cycles can clearly and intuitively reflect the surface characteristics of the electrode material.
[0138] Before characterization and analysis, the samples were pretreated. The specific steps are as follows: In a glove box filled with inert gas, carefully disassemble the battery to be tested, remove the electrode sheet from the battery, and immerse it in a pre-prepared ethyl methyl carbonate (EMC) solution to thoroughly remove the residual electrolyte on the electrode surface. After cleaning, place the electrode sheet in a vacuum drying oven for drying. Subsequently, a TECSAN AMBER GMH scanning electron microscope was used to collect and analyze images of the sample surface. The results are shown in Fig.13 ( Fig.13 (a), (b), (c) are the morphology images of comparative example 1 after cycle at 200nm, 20um, and 10um, respectively; (d), (e), and (f) are the morphology images of embodiment 1 after cycle at 200nm, 20um, and 10um, respectively).
[0139] Depend on Fig.13 It can be seen that the electrolyte electrode obtained in Comparative Example 1 has obvious unevenness on the surface after the cycle, which is manifested as numerous small granular protrusions, the surface is extremely rough, and significant cracks and pores are observed in some areas. These surface defects are likely to be the reason for the rapid decay or even damage of battery performance during the cycle. However, the battery surface corresponding to the electrolyte obtained in Example 1, to which an appropriate amount of tris(2,2,2-trifluoroethyl) phosphate and aluminum isopropoxide are added, appears quite smooth after the cycle, and the overall appearance is flat, and no obvious cracks are found, which reflects that the stability of the battery during the cycle has been significantly improved, and its electrochemical performance has therefore been significantly improved.
[0140] 13. At the same time, high-resolution transmission electron microscopy (HRTEM) was used to characterize the microstructure of the lithium-rich manganese-based electrode material after 200 cycles. The Talos F200x high-resolution transmission electron microscope produced by FEI was used to observe the electrode / electrolyte interface film (CEI film) on the surface of the electrode material after recycling. The results are shown in Figure 14-15 .
[0141] Depend on Figure 14-15It can be seen that the CEI morphology of the electrolyte electrode obtained in Comparative Example 1 after cycling is uneven, the shape is relatively fuzzy, and its thickness is measured to be about 12nm, while the CEI film surface of the battery corresponding to the electrolyte obtained in Example 1 with the addition of an appropriate amount of tris(2,2,2-trifluoroethyl) phosphate and aluminum isopropoxide is relatively smooth and uniform, with a denser structure and a thinner thickness, and the measured thickness is 4-6nm. The CEI film obtained in the present invention, due to its dense and uniform characteristics, more effectively protects the positive electrode material, reduces the side reaction between the electrode and the electrolyte, and thus helps to extend the service life of the battery.
[0142] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A non-flammable electrolyte for lithium-ion batteries, characterized in that: The invention comprises an organic solvent, a lithium salt, a fluorophosphate ester and a film-forming additive, wherein the film-forming additive is aluminum isopropoxide.
2. The non-flammable electrolyte for lithium-ion batteries according to claim 1, characterized in that: The organic solvent comprises cyclic carbonate and linear carbonate, the cyclic carbonate is at least one of ethylene carbonate and propylene carbonate, and the linear carbonate is at least one of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
3. The non-flammable electrolyte for lithium-ion batteries according to claim 1, characterized in that: The lithium salt is at least one of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium dioxalatoborate, lithium bis(trifluoromethylsulfonylimide) and lithium bis(fluorosulfonylimide).
4. The non-flammable electrolyte for lithium-ion batteries according to claim 1, characterized in that: The fluorophosphate ester is tris(2,2,2-trifluoroethyl) phosphate.
5. The non-flammable electrolyte for lithium-ion batteries according to claim 1, characterized in that: The concentration of lithium salt in the electrolyte is 0.5-2 mol / L.
6. The non-flammable electrolyte for lithium-ion batteries according to claim 1, characterized in that: The concentration of the fluorophosphate in the electrolyte is 8-20 wt %.
7. The non-flammable electrolyte for lithium-ion batteries according to claim 1, characterized in that: The concentration of the film-forming additive in the electrolyte is 0.5-2 wt %.
8. The method for preparing the non-flammable electrolyte for lithium ion batteries according to claim 1, characterized in that: The following steps are involved: (1) mixing an organic solvent and a lithium salt, heating and stirring, to prepare a basic electrolyte; (2) Adding fluorophosphate and film-forming additives to the basic electrolyte prepared in step (1), heating and stirring, to prepare a non-flammable electrolyte for lithium-ion batteries.
9. The method for preparing a non-flammable electrolyte for lithium-ion batteries according to claim 8, characterized in that: In steps (1)-(2), the heating temperature is 30-50°C.
10. Use of the non-flammable electrolyte for lithium ion batteries according to claim 9 in the preparation of lithium ion batteries.
Citation Information
Cited By
Aluminum alkoxide-phosphate / phosphite electrolyte and preparation method and application thereof
CN121905958A